2021
DOI: 10.2147/ijgm.s291864
|View full text |Cite
|
Sign up to set email alerts
|

Using Thromboelastography to Predict Blood Loss After Off-Pump Coronary Artery Bypass Grafting

Abstract: Objective: This study aims to investigate the value of thromboelastography (TEG) in predicting blood loss, and its relationship with blood transfusion demand, during the perioperative period in off-pump coronary artery bypass grafting (OPCABG). Methods: The data of 398 patients undergoing OPCABG were retrospectively analyzed. Blood was drawn before anesthesia induction (T1) and at 10 minutes after heparin neutralization (T2) for further TEG detection. The patients were divided into two groups based on the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…The ability of TEG parameters to predict bleeding was questionable in the literature as some studies showed that the use of TEG-MA, TEG R-time, TEG-K, and TEG α-angle was also predictive of blood loss during the operation [75,[79][80][81][82][83][84][85][86][87][88] and even postoperatively [89][90][91][92][93][94][95][96]. They could also predict short-term bleeding complications and micro-bleeding [97,98].…”
Section: Bleeding Predictionmentioning
confidence: 99%
“…The ability of TEG parameters to predict bleeding was questionable in the literature as some studies showed that the use of TEG-MA, TEG R-time, TEG-K, and TEG α-angle was also predictive of blood loss during the operation [75,[79][80][81][82][83][84][85][86][87][88] and even postoperatively [89][90][91][92][93][94][95][96]. They could also predict short-term bleeding complications and micro-bleeding [97,98].…”
Section: Bleeding Predictionmentioning
confidence: 99%